Effects of sanitation and hygiene perceptions on international travelers' health, travel plans and trip experiences in India - Chandra, Rishita; Supehia, Sakshi; Nath, Bhola; Chhetri, Charu; Kumari, Ranjeeta; Joshi, Kumari Damayanti; Sharma, Roshan; Chaudary, Jatin; Joshi, Kishor; Bhatta, Ramesh; Bhatt, Chhavi R. (Frontiers in Public Health, 2022)
Background International travelers often experience travelers' diarrhea. However, there is paucity of data on whether self-reported gastrointestinal symptoms influence travelers' perceptions of adequacy of sanitation and hygiene services encountered during travel, and to what degree their travel plans, and overall trip experience are impacted. Methods A cross-sectional face-to-face survey was conducted amongst international travelers in India. Data collected included socio-demographics, travel characteristics, self-reported occurrence and frequency/severity of gastrointestinal symptoms, perceptions of sanitation and hygiene encountered, and adverse effects of symptoms on travel plans and trip experiences. Chi-square tests and logistic regression were performed to describe differences and associations between categorical variables. Results Of the 300 international travelers surveyed, 46.3% experienced diarrhea. At least two thirds of travelers perceived the quality of sanitation (67.0%) and hygiene (70.0%) encountered to be inadequate. Perceptions of inadequate sanitation (adjusted OR = 3.0; 95% CI 1.7–5.5) and poor hygiene (adjusted OR = 7.7; 95% CI 4.1–15.5) were higher among travelers who experienced diarrhea. Additionally, both higher likelihood of travel plans being affected (adjusted OR = 10.7; 95% CI 5.1–23.6) and adverse impacts on overall trip experience (adjusted OR = 2.8; 95% CI 1.4–5.8) were reported among those who experienced diarrhea. Conclusions More than two thirds of travelers surveyed in India experienced inadequate sanitation and hygiene services, with perceptions influenced by occurrence and frequency of diarrhea. Self-reported diarrhea was also associated with adverse effects on travel plans and overall trip experience. While these results may seem intuitive, they have important implications and suggest that improving sanitation and hygiene standards in India could potentially enhance tourism.